6(7x-3)=37

Simple and best practice solution for 6(7x-3)=37 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(7x-3)=37 equation:


Simplifying
6(7x + -3) = 37

Reorder the terms:
6(-3 + 7x) = 37
(-3 * 6 + 7x * 6) = 37
(-18 + 42x) = 37

Solving
-18 + 42x = 37

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 42x = 37 + 18

Combine like terms: -18 + 18 = 0
0 + 42x = 37 + 18
42x = 37 + 18

Combine like terms: 37 + 18 = 55
42x = 55

Divide each side by '42'.
x = 1.30952381

Simplifying
x = 1.30952381

See similar equations:

| (3-4x/6)-(1-2x/12)=-2 | | -7(2C+5)=3(c-6) | | 17500000+550x=3500000+48*35x | | -5(5+6r)=95 | | 161-5x=14-9x | | -(4y+4)-(-3y-7)=3 | | 144+400=c^2 | | (2-x/2)-(1-5x/8)=-1 | | 8(2+8x)=336 | | c/5+2=19 | | -96=-8(4x-4) | | y/4-3=4 | | 3/4x6/5 | | -264=-8(5n+3) | | -6c+4/9=4 | | 3/4/5/6 | | n^2-2n+1=6 | | 4x/3+4=44 | | q+25=29 | | p-19=-10 | | -2n=-62.9 | | -12(x-6)=33(x+64) | | 12k=732 | | 3(x+z)+75=y | | 7j=637 | | h-14=-11 | | 12(4x-7)=4(12x+8) | | x^2+2x-677=0 | | 3g-14=34 | | -7-x=6 | | 5x+10=7x+8 | | 5x^3=5x^3 |

Equations solver categories